THE INFLUENCE OF BRAND IMAGE AND PRICE ON THE PURCHASE DECISION OF SKECHERS SHOES IN STUDENTS OF TRISAKTI SCHOOL OF TOURISM - Ismeth Emier Osman (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of brand image and price on the decision to purchase Skechers shoes for Trisakti School of Tourism. This type of research is descriptive quantitative research with multiple regression analysis. The collection technique was by distributing questionnaires with a Liker scale from 1 to 5. The population in this study were all students of Trisakti School of Tourism, while the total sample was 100 respondents. Sampling technique with accidental sampling. The results of the study partially show that the brand image and price of Skechers shoes have a significant effect on the purchasing decisions of Trisakti School of Tourism students because a good brand image on high quality and good Skechers shoes will result in a high purchasing decision as well, then the price is in accordance with the quality. products so that consumers will decide to buy products whose price is judged according to the quality of the product or not too expensive.